Immunotherapy in People With HIV and Cancer - Puronen, Camille E.; Ford, Emily S.; Uldrick, Thomas S. (Frontiers in Immunology, 2019)
HIV infection increases the risk of cancer. HIV-associated lymphocytopenia and immune dysregulation permit immune evasion of oncogenic viruses and premalignant lesions. Various types of immunotherapy, including monoclonal antibodies, interferon, cytokines, immunomodulatory drugs (IMiDs), allogeneic hematopoietic stem cell transplant, and most importantly ART have shown efficacy in HIV-related cancer. Emerging data suggest that checkpoint inhibitors targeting the PD-1/PD-L1 pathway can be safe and effective in people with HIV and cancer. Cancer immunotherapies may also affect HIV latency reversal, HIV-specific immunity, and the viral reservoir. Studying immunotherapy in people with HIV and cancer presents a unique opportunity to gain insight into mechanisms for HIV eradication.